PENINGKATAN HASIL BELAJAR GERAK DASAR LEMPARAN MELALUI PERMAINAN BOLA PANAS (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study is to increase learning outcomes about basic throwing motion through the hot ball game for student at class IV Sendang Elementary School Wonotunggal Batang in 2013. From the research data is known that there is an increase in the percentage of completeness results in the classical study of the cognitive aspects of 72.73% in the first cycle increased to 81.82% in the second cycle. For psychomotor aspects of learning outcomes increased from 57.58% in the first cycle to 84.85% in the second cycle. As for the affective aspects of learning outcomes obtained a value of 78.79% in the first cycle increased to 84.85% in the second cycle. Based on the results obtained the conclusion that through the hot ball games can improve learning outcomes basic motion throws for student at class IV Sendang Elementary School Wonotunggal Batang Year 2013.